2012
DOI: 10.1161/strokeaha.112.660373
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Perconditioning Is Effective Alone and in Combination With Intravenous Tissue-Type Plasminogen Activator in Murine Model of Embolic Stroke

Abstract: Background and Purpose Remote ischemic conditioning is cardioprotective in myocardial infarction and neuroprotective in mechanical occlusion models of stroke. However, there is no report on its therapeutic potential in a physiologically relevant embolic stroke model (eMCAO) in combination with intravenous (IV) tissue plasminogen activator (tPA). Methods We tested remote ischemic perconditioning therapy (RIPerC) at 2 hours after eMCAO in the mouse with and without IV tPA at 4 hours. We assessed cerebral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
153
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(163 citation statements)
references
References 32 publications
8
153
1
1
Order By: Relevance
“…Emerging clinical trials have corroborated the previous research, suggesting that remote preconditioning may indeed protect the heart [9][10][11]. In addition, recent findings in experimental animal models and clinical studies suggest that remote ischemic preconditioning may also be beneficial to the brain without exacerbating intracerebral hemorrhage [12][13][14][15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 55%
“…Emerging clinical trials have corroborated the previous research, suggesting that remote preconditioning may indeed protect the heart [9][10][11]. In addition, recent findings in experimental animal models and clinical studies suggest that remote ischemic preconditioning may also be beneficial to the brain without exacerbating intracerebral hemorrhage [12][13][14][15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 55%
“…5,6 In a recent study, rPerC was found to be effective alone and in combination with rtPA in a murine stroke model. 7 The protective effect seemingly involves the activation of multiple endogenous defense mechanisms. These include an upregulation of nitric oxide levels, improved cerebral blood flow in the ischemic penumbra, and downregulation of inflammation and glutamatergic excitotoxicity.…”
Section: Strokementioning
confidence: 99%
“…Our study is the first evaluate of the potential protective effect of PER alone or combined with POS on kidney IR-induced injury, that only be test before in myocardium 15,20 , brain 17,26 , and liver 18 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Based on fact that perconditioning is performed in a distant tissue, is a non-invasive procedure and do not increase the surgical time, thus does not require direct access to the artery and could be easily applied during the surgery or endovascular surgery [15][16][17][18][19] ; this ischemic conditioning must be test in human IR syndromes 20,31 . However, new studies aim to understanding the mechanism are need 32 .…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation